Patient’s Satisfaction with Healthcare Services in Out Patient Department of a Tertiary Cardiac Centre in Nepal - Dhungana, Suraksha; Prajapati, Dipanker; Khadka, Sunita; Dangol, Prati Badan; Dhungana, Murari; Dangol, Nita Devi; Saru, Deoki; Shakya, Roji; Luitel, Kopila; Thakuri, Shanta Singh; Adhikari, Chandra Mani (Nepalese Heart Journal, 2023)
Background and Aims: Patient’s satisfaction with the healthcare services is important because evidence suggests that satisfied patients are more adherent to treatment guidelines and have better clinical outcomes. We aim to assess the patients’ satisfaction with healthcare services in a tertiary cardiac centre of Nepal. Methods: We conducted a descriptive cross sectional study to collect the data by convenience sampling method from 365 patients who attended the out-patient Department of Shahid Gangalal National Heart Centre from December 2021 to March 2022. In this study a validated tool was used after translation into Nepali language. A semi structured face to face interview schedule was used to collect data from the patients, which was then filled in Kobo Toolbox; the web based questionnaires and were analyzed. Results: Overall satisfaction rate of the patients with the health care services provided by a tertiary cardiac center was 91.25%. In this study, 89.86% were satisfied with physical facilities, 91.24% with registration and pharmacy services, 93.36% with physicians and nurses’ services and 90.56% with other services. Conclusion: In this study, most of the participants were highly satisfied with the services provided by the hospital. However, the feedback from this study can be used for the improvement of the health care services which could be beneficial for the hospital as well as cardiac patients with overall benefit in cardiovascular outcome.